A bi-phasic modelling approach for interlaminar and intralaminar damage in the matrix of composite laminates. (15th February 2020) - Airoldi, Alessandro; Mirani, Chiara; Principito, Lucia
Abstract: The paper presents a new bi-phasic approach to model delamination and transverse cracking in the matrix of composite laminates by using a single constitutive law, based on a decomposition of the composite stiffness properties into idealized fibre and matrix phases. The decomposition is used in finite element models where membrane elements representing the fibre phase are embedded in a three-dimensional mesh that models the matrix phase. A single constitutive law is applied to the matrix phase by combining a Cohesive Zone Model, which models delamination between plies, with an intralaminar damage law, aimed at modelling a transverse matrix cracking within the plies. All the theoretical aspects of decomposition and constitutive law are described. Then, the numerical experimental correlations are presented considering delamination tests and the evolution of the transverse matrix cracking in cross-ply specimens, with a statistical distribution of strength properties, also in the presence of interactions between matrix cracking and delamination. The approach provides the possibility to efficiently simulate both individual delaminations and transverse cracks with a model using a single layer of elements per ply, without introducing interface elements. Moreover, it also provides new possibilities to control the interaction between intralaminar and interlaminar damage phenomena.